GaCl3‐Mediated Reactions of Donor–Acceptor Cyclopropanes with Aromatic Aldehydes. Issue 40 (30th August 2016) - Borisov, Denis D.; Novikov, Roman A.; Tomilov, Yury V.
Abstract: A new strategy for cascade assembly of substituted indenes and polycyclic lactones based on reactions of donor–acceptor cyclopropanes and styrylmalonates with aromatic aldehydes in the presence of GaCl3 has been developed. The use of GaCl3 makes it possible to principally change the direction of the reaction known in this series of substrates and to perform the process in a multicomponent version. Generation of formal 1, 2‐zwitterionic intermediates owing to complexation of dicarboxylate groups with GaCl3 is the driving force of the reactions discovered. This method makes it possible to assemble indenylmalonates or indano[ 1′, 2′:2, 3 ]indano[ 2, 1‐b ]furan‐2‐ones in one synthetic stage from readily available starting compounds with high regio‐ and diastereoselectivity. A mechanism of the reactions has been suggested using the 18 O label in benzaldehyde. Abstract : Old reagents, new products : A new strategy for the cascade assembly of substituted indenes and polycyclic lactones based on reactions of donor–acceptor cyclopropanes and styrylmalonates with aromatic aldehydes has been developed. Use of GaCl3 makes it possible to change the direction of the reaction and to perform the process in a multicomponent version (27 examples).